Ecotourism Product Development Strategy at Bunder Forest Park in Gunung Kidul - Syaharani, Nabilla Rasya; Prayuda, Rizal Arya; Nurjuita, ike; supriyadi, supriyadi; agustina, ana (Sriwijaya Journal of Environment, 2025)
Conservation area in Tahura Bunder has the potential for natural resources and environmental services that can supply the strengthening of the tourism sector. Special interest nature tourism through educational tourism/educational tourism is a special attraction. The strategy for developing educational tourism is a great opportunity in developing educational tourism. For this reason, this research is important in analyzing these opportunities. This research was conducted on March, 2024, taking qualitative data in the form of descriptive information, narratives, images, or symbols which were then analyzed using an inductive approach with quantitative descriptive analysis. The results of the study show that there is potential for landscapes and views that can be developed, as well as SWOT and alternative approaches that can be taken for the development of the BunderForest Park as an ecotourism product. landscapes and views that can be developed.